Yield and quality of soybean seeds inoculated with Bacillus subtilis strains - Tauan R. Tavanti; Renan F. R. Tavanti; Fernando S. Galindo; Isadora Simões; Larissa S. Dameto; Marco E. de Sá (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of growth-promoting bacteria can increase the yield and quality of seeds of several annual crops, such as soybean. Based on that, the present study aimed to evaluate the effects of the inoculation of Bacillus subtilis strains on seed treatment, evaluating the yield and quality of seeds of two soybean cultivars. The experiment was conducted in a conventional system, in an Oxisol of clayey texture, in a crop under sprinkler irrigation. The experimental design was randomized blocks, arranged in split plots with four repetitions. Treatments were composed, in the plots, of two soybean cultivars: M7110 IPRO and Brasmax Desafio RR. Within the levels of subplots, the treatments consisted of inoculation and doses of inoculant: Bacillus subtilis Pant001 strain at doses of 0, 2, 3, 4 and 5 mL kg-1, and QST713 strain at the recommended dose of 2 mL kg-1. Inoculation with the strains Pant001 and QST713 increased the yield of both soybean cultivars tested, besides improving seed quality due to the increase in the concentration of total storage proteins, seedling emergence percentage and seed vigor by the accelerated aging test.